Lahar at Kali Konto after the 2014 Eruption of Kelud Volcano, East Java: Impacts and Risk - Suprapto Dibyosaputro; Gilang Arya Dipayana; Henky Nugraha; Kartika Pratiwi; Hogy Prima Valeda (Universitas Muhammadiyah Surakarta, 2015)
Five days after the Kelud Volcano eruption of 13 February 2014, lahar occurred in several channels of the Volcano. Rainfall with intensity of 26 mm/hour mobilized pyroclastic material from the upper slopes of Kelud Volcano down the channel during 3.5 hour. Using this eruption as a case study, the aims of this paper are (1) to study the geomorphic impact of lahars and (2) to study future hazards and risks due to the potential of lahar source material and lahar repose area. To reach these two goals, we use both primary and secondary data. The primary data comprises an integration of remote sensing, GIS approach, and fieldwork control, in order to investigate the geomorphic impacts of lahars. Secondary data were collected through interviews and statistical approach in villages, in order to determine their perception to the risk of lahar. Morphogenic processes such as riverbank erosion, channel-widening and riverbed downcutting took an important role in generating the impact of lahar in Kali Konto. The medial and distal areas were affected more largely affected than the proximal area. This major impacts have been river widening and buried crop field inside of the channel. This result allowed us to provide recommendation to population living along those areas at risk, in order to be prepared against the eventuality of potentially large and destructive lahars.